Evaluasi pengelolaan limbah B3 cair proses produksi pada industri manufaktur di PT. Z, Kota Bandung - Wiryawan, Ikhsan Rifqi; Pharmawati, Kancitra (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2024)
The disposal of hazardous and toxic waste (B3) originating from production processes can have negative effects on human health and the environment. PT. Z is a manufacturing industry that produces B3 waste as a result of its production activities. The presence of B3 waste requires proper management to avoid negative impacts. There are three types of waste produced: water coolant, expired chemicals, and used oil, each with characteristics that need to be well-managed. The research aims to assess the suitability level of hazardous and toxic waste management at PT. Z based on applicable regulations. In the research, data collection methods include both primary and secondary data, with data processing using Likert scale scoring. The research variables include the reduction, packaging, labeling and symbolizing, and storage of hazardous and toxic waste It was found that there were discrepancies in the variables of packaging, labeling, and symbolizing between the existing conditions and the regulations. The evaluation results indicate that hazardous waste management at PT. Z achieved a score of 90.32%, which is categorized as very good.